2013
DOI: 10.1038/nrd4176
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic opportunities of the IL-22–IL-22R1 system

Abstract: Interleukin-22 (IL-22) is a key effector molecule that is produced by activated T cells, including T helper 22 (TH22) cells, TH17 cells and TH1 cells, as well as subsets of innate lymphoid cells. Although IL-22 can act synergistically with IL-17 or tumour necrosis factor, some important functions of IL-22 are unique to this cytokine. Data obtained over the past few years indicate that the IL-22-IL-22 receptor subunit 1 (IL-22R1) system has a high potential clinical relevance in psoriasis, ulcerative colitis, g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
485
1
13

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 497 publications
(518 citation statements)
references
References 170 publications
19
485
1
13
Order By: Relevance
“…Thereby, NCR + ILC3 suppress further tissue damage, alloreactive T cell activation and the occurrence of GVHD (Figure 2) 31. Furthermore, IL‐22 cytokine‐based therapy has already been considered for prevention of GVHD and lung transplantation complications 37. The active status and gut/skin homing receptor expression of ILC, especially the IL‐22‐producing ILC3, seems to minimize GVHD development following HCT.…”
Section: Potential Of Il‐22 Producing Ilc3 In Gvhd Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Thereby, NCR + ILC3 suppress further tissue damage, alloreactive T cell activation and the occurrence of GVHD (Figure 2) 31. Furthermore, IL‐22 cytokine‐based therapy has already been considered for prevention of GVHD and lung transplantation complications 37. The active status and gut/skin homing receptor expression of ILC, especially the IL‐22‐producing ILC3, seems to minimize GVHD development following HCT.…”
Section: Potential Of Il‐22 Producing Ilc3 In Gvhd Therapymentioning
confidence: 99%
“…IL‐22 could be a relatively safe target in enhancing mucosal healing, since it does not directly affect immune cell functions. However, possible adverse effects might occur, for example, due to dysregulated responses of keratinocytes in the skin 20, 37. Of note, in an earlier large‐scale clinical study investigating human gastrointestinal GVHD risk factors, Reg3α protein was identified as indicator of higher incidence for developing GVHD after allo‐HCT 38.…”
Section: Potential Of Il‐22 Producing Ilc3 In Gvhd Therapymentioning
confidence: 99%
“…ILC3s are a group of lymphocytes without T‐cell‐specific antigen receptors with particular accumulation at mucosal sites and serve as key regulators during intestinal inflammation 18, 19, 20, 21. ILC3s can rapidly respond to external stimuli and play critical roles in host defense, the resolution of inflammation and initiation of tissue repair in the gut 21, 22, 23, 24, 25, 26. These protective effects of ILC3s are mostly dependent on their production of the reparative cytokine IL‐22.…”
Section: Introductionmentioning
confidence: 99%
“…These protective effects of ILC3s are mostly dependent on their production of the reparative cytokine IL‐22. By binding to its receptor on epithelial cells, IL‐22 contributes to production of antimicrobial peptides and mucins, regulation of gut microbiota, maintenance of the gut barrier function and amelioration of intestinal inflammation 25, 26. But it remains unclear how ILC3s are activated and regulated during intestinal inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…Interleukin-22 has been the focus of emerging research in a variety of systemic inflammatory diseases and it has been identified as a key regulator of host defense acting directly at the mucosal barriers [10,11]. Little is known about IL-22 and reproductive function.…”
Section: Introductionmentioning
confidence: 99%